1999
DOI: 10.1037/1076-8971.5.3.556
|View full text |Cite
|
Sign up to set email alerts
|

An interdisciplinary approach to understanding social sexual conduct at work.

Abstract: The authors reviewed the most recent U.S. Supreme Court holdings regarding sexual harassment (SH) and compared them to legal commentators' calls for reform in the law. Because the courts have ignored empirical evidence, and agreement among social forces is lacking, the judiciary has been unable to send a unified message to regulate social sexual misconduct at work. This analysis of recent social science research suggests that the a more thorough understanding of the fundamentals of SH law is needed. The author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 87 publications
(169 reference statements)
0
46
0
Order By: Relevance
“…They have found a correlation between sexual harassment and hostile attitudes toward women (Mazer and Percival 1989;Reilly et al 1986;Wiener and Gutek 1999;Wiener and Hurt 1999). Women were found more likely to be sexually harassed when they do not comply with the prescriptive gender stereotypes which serve to maintain power inequality (Burgess and Borgida 1999).…”
Section: The Association Between Sexual Harassment and Attitudes Towamentioning
confidence: 95%
“…They have found a correlation between sexual harassment and hostile attitudes toward women (Mazer and Percival 1989;Reilly et al 1986;Wiener and Gutek 1999;Wiener and Hurt 1999). Women were found more likely to be sexually harassed when they do not comply with the prescriptive gender stereotypes which serve to maintain power inequality (Burgess and Borgida 1999).…”
Section: The Association Between Sexual Harassment and Attitudes Towamentioning
confidence: 95%
“…Accordingly, workers reach a preliminary judgment based on wellrehearsed and easily retrievable attitude structures. Prior research (Wiener & Hurt, 1999Wiener et al, 2002) demonstrated that at least two attitude structures, hostile sexism (i.e., women are aggressive and must be kept in their place through gender dominance) and benevolent sexism (i.e., woman are weak and should be protected from overbearing men) (Glick & Fiske, 1996), influence the perceptions of hostile work environment harassment. Workers and students who score high on the hostile (benevolent) sexism scale harbor antipathetic (protectionist) attitudes toward female harassment complainants and find less (more) evidence that they are victims of workplace discrimination.…”
mentioning
confidence: 99%
“…Recent social psychological theory suggests that people may evaluate allegations of sexual harassment with various amounts of cognitive effort (Wiener & Hurt, 1999Wiener et al, 2002). Accordingly, workers reach a preliminary judgment based on wellrehearsed and easily retrievable attitude structures.…”
mentioning
confidence: 99%
“…7 This gender gap in perceptions appears to be larger regarding more ambiguous, hostile environment behaviors than quid pro quo behaviors (see Baird et al 1995; Frazier, Cochran & Olson 1995; Rotundo, Nguyen & Sackett 2001; Thacker & Gohmann 1993). Some point to this research as providing evidence in support of the use of a reasonable woman standard, as contrasted with a reasonable person standard, in sexual harassment court cases involving female plaintiffs (see Wiener et al 1997; Wiener & Hunt 1999). For our purposes, this literature highlights the importance of taking into account gender differences in any investigation of worker perceptions of sexual harassment.…”
Section: Influences On Perceptions Of Sexual Harassmentmentioning
confidence: 90%